2020
DOI: 10.1186/s12884-020-2719-3
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum haemorrhage (PPH) rates in randomized trials of PPH prophylactic interventions and the effect of underlying participant PPH risk: a meta-analysis

Abstract: Background: Postpartum haemorrhage (PPH) remains a leading cause of maternal mortality. Many trials assessing interventions to prevent PPH base their data on low risk women. It is important to consider the impact data collection methods may have on these results. This review aims to assess trials of PPH prophylaxis by grading trials according to the degree of risk status of the population enrolled in these trials and identify differences in the PPH rates of low risk and high risk populations. Methods: Systemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 51 publications
(108 reference statements)
0
11
0
2
Order By: Relevance
“…It is classified as: Minor PPH (blood loss 500-1000 ml) and major PPH (more than 1000 ml). Almost 500,000 women die due to this preventable cause each year, especially hemorrhage that occurred at time of delivery (4) . Other nonfatal complications may occur as Sheehan's syndrome (Pituitary infarction), coagulopathy, and organ damage due to hypotension, shock, and risk of hysterectomy (5) .…”
Section: Introductionmentioning
confidence: 99%
“…It is classified as: Minor PPH (blood loss 500-1000 ml) and major PPH (more than 1000 ml). Almost 500,000 women die due to this preventable cause each year, especially hemorrhage that occurred at time of delivery (4) . Other nonfatal complications may occur as Sheehan's syndrome (Pituitary infarction), coagulopathy, and organ damage due to hypotension, shock, and risk of hysterectomy (5) .…”
Section: Introductionmentioning
confidence: 99%
“…Further to this, the rate of instrumental vaginal births in our study was ~21–24%, compared with ~4% in CHAMPION. Instrumental vaginal birth is an important risk factor for PPH, 23 and complex births may be under‐represented in trials used to estimate PPH incidence 24 …”
Section: Discussionmentioning
confidence: 99%
“…Instrumental vaginal birth is an important risk factor for PPH, 23 and complex births may be underrepresented in trials used to estimate PPH incidence. 24 There is insufficient evidence to support one method of blood loss estimation over another, 25 including acceptability to women. We made efforts to exclude liquor and combined volumetric and gravimetric measurement of blood loss by using direct collection of blood along with weighing blood-soaked swabs and linen, excluding dry weights.…”
Section: Discussionmentioning
confidence: 99%
“…According to Evensen, Anderson, & Fontaine (2017), postpartum hemorrhage can occur in patients without risk factors for hemorrhage, and around 20% of PPH occurs in women with no risk factors. A study reviewed by Hawker & Weeks (2020), also showed that antenatal risk factors might not significantly contribute to the PPH rates while the method of birth could have more impact. It means that mothers can develop obstetric complications even with no risk factors.…”
Section: Obstetric Complicationmentioning
confidence: 99%